2016
DOI: 10.4278/ajhp.121127-quan-576
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Activity and Metabolic Syndrome: Comparison between Self-Report and Accelerometry

Abstract: Individuals who do not meet the PA guidelines exhibited greater odds of having metabolic syndrome. This relationship tended to be stronger for objective PA measures than for self-report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…We show that the association with successful ageing was more pronounced for MVPA assessed by accelerometer compared to questionnaire. Previous studies have also shown objective assessments of physical activity to be more strongly associated with metabolic syndrome45, biomarkers46 and obesity indicators37. Taken together these findings suggest that measurement error inherent to self-reported physical activity measures leads to misclassification, attenuating associations with health outcomes47.…”
Section: Discussionmentioning
confidence: 71%
“…We show that the association with successful ageing was more pronounced for MVPA assessed by accelerometer compared to questionnaire. Previous studies have also shown objective assessments of physical activity to be more strongly associated with metabolic syndrome45, biomarkers46 and obesity indicators37. Taken together these findings suggest that measurement error inherent to self-reported physical activity measures leads to misclassification, attenuating associations with health outcomes47.…”
Section: Discussionmentioning
confidence: 71%
“…The nature of many common PA questionnaires lend themselves to significant over-reporting of daily PA levels (Atienza et al, 2011; Belcher et al, 2014; Schuna Jr et al, 2013; Tucker, Welk & Beyler, 2011; Tucker et al, 2015), as participants are asked to report domain-based PA levels (i.e., transport, occupation and leisure time), and inaccuracy can also arise because some questionnaires often request participants to only report PA when they engage in PA during periods of at least 10-mins. Due to the social desirability of portraying oneself as engaging in healthy behaviors, e.g., being physically active, survey participants often report higher than actual levels of healthful behaviors (Klesges et al, 2004; Phillips & Clancy, 1972), and this bias may differ according to sex, socio-economic status and other characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…use logistic regression to look at the probability of having MetS for a given level of usual activity (see for example, Tucker et al (2016) or Sisson et al (2010)). The results consistently say that those who exercise less have a higher probability for MetS.…”
Section: The Benefits Of Physical Activitymentioning
confidence: 99%
“…Recall someone is defined as having MetS if she has a combination of high blood pressure, high blood sugar, high body fat-especially around the waist, and high (low) LDL (HDL) and triglyceride levels. There are fairly well established cut offs for what constitutes "high" levels for each of the previous measures (Tucker et al (2016)). And a common classifier is if one has at least three measures that are "high", then he is said to have…”
Section: The Benefits Of Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation